Synthesis and characterisation of AlMgB14 and AlMgB14-Ni3Al composites. (2018) - Zhou, Y.M.; Zhang, F.L.; Bai, K.; Zhang, T.; Huang, H.P.; Wu, S.H.; Luo, S.M.
Materials with higher hardness and lower friction coefficients with steel have been proposed as candidates for strategic use in the application fields of cutting tool and friction reduction materials. Aluminium magnesium boride (AlMgB14 ) and its composites are excellent candidates for these purposes. The impurity of MgAl2 O4 is normally formed in the synthesised AlMgB14 because of oxygen and oxide involved from raw materials and processing, so an extra amount of Al and Mg beyond the stoichiometric ratio of AlMgB14 were introduced into the raw elemental powders to synthesise AlMgB14 in an atmosphere of argon at 1, 500°C. The AlMgB14 -Ni3 Al composites were also synthesised by hot pressed sintering at 1, 450°C and 1, 600°C separately. The microstructure and mechanical properties of AlMgB14 and AlMgB14 -Ni3 Al composites were also examined. The results showed that extra addition of 5 wt.% Al and 5 wt.% Mg can reduce the production of MgAl2 O4 in the formation of AlMgB14 . Besides of AlMgB14 and MgAEO4, Ni3 Al and NiAl are identified in the AlMgB14 -Ni3 Al composites, the hardness and fracture toughness of AlMgB14 -Ni3 Al composites are decreased with higher content of Ni3 Al due to the present of Ni3 Al and NiAl phase.